The relationship between internet access frequency, attitudes towards the internet and internet self-efficacy and behaviour intention in using the internet among secondary school students - Ismail, Nurul Hafizah; Mohd Ayub, Ahmad Fauzi; Wong, Su Luan (Universiti Putra Malaysia Press, 2016)
This study identifies several specific factors that influence students’ behaviour intention using internet competently. A total of 262 secondary school students taking the Information and Communication Technology Literacy (ICTL) course were randomly chosen. The study revealed the respondents had positive attitudes towards the internet with an average mean score of 3.78 (SD = .47) on a Likert scale of 1-5. The results also indicated a high level of internet self-efficacy (M = 3.71, SD = 0.54) and behavioural intention in using the internet (M = 4.22, SD = .51) Correlation analyses showed internet self-efficacy, attitude towards internet and internet access frequency had positive relationships with students’ behaviour intention in using the internet. Nevertheless, a multiple regression analysis revealed only internet self-efficacy and internet access frequency had significant influence on students’ attitudes towards using computers in the classroom.